2018
DOI: 10.1134/s0006297918080059
|View full text |Cite
|
Sign up to set email alerts
|

Structural Alterations in Human Fibroblast Growth Factor Receptors in Carcinogenesis

Abstract: Fibroblast growth factor (FGF) plays an important role in human embryogenesis, angiogenesis, cell proliferation, and differentiation. Carcinogenesis is accompanied by aberrant constitutive activation of FGF receptors (FGFRs) resulting from missense mutation in the FGFR1-4 genes, generation of chimeric oncogenes, FGFR1-4 gene amplification, alternative splicing shift toward formation of mesenchymal FGFR isoforms, and FGFR overexpression. Altogether, these alterations contribute to auto- and paracrine stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…It plays a role in regulating excessive activation of the FGF-FGFR1 signaling pathway [ 4 , 5 ]. The signaling axis of FGFRs is primarily activated in a ligand-dependent manner, by binding of fibroblast growth factors (FGFs) and the subsequent receptor dimerization induced intracellular kinase transautophosphorylation events [ 6 ]. Meanwhile, FGFRs can also be activated in a ligand-independent manner, such as chromosome translocation induced FGFRs gene fusion with other constitutively expressed genes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It plays a role in regulating excessive activation of the FGF-FGFR1 signaling pathway [ 4 , 5 ]. The signaling axis of FGFRs is primarily activated in a ligand-dependent manner, by binding of fibroblast growth factors (FGFs) and the subsequent receptor dimerization induced intracellular kinase transautophosphorylation events [ 6 ]. Meanwhile, FGFRs can also be activated in a ligand-independent manner, such as chromosome translocation induced FGFRs gene fusion with other constitutively expressed genes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The specific interaction of FGFs-FGFRs with cofactors activates several intracellular cascades, including Ras/MAPK, PI3K/Akt, and PLCγ/PKC pathways, to regulate target genes transcription (Katoh and Nakagama, 2014). Abnormalities of FGFs/FGFRs will lead to many diseases and are considered as a risk factor in the development of cancer (Itoh, 2010;Touat et al, 2015;Mikhaylenko et al, 2018). The gene transcription level (Figure 1A) and mutation status of (Figure 1B) FGFs/FGFRs were also investigated in HCC patients based on GEPIA2 and cBioPortal database (Cerami et al, 2012;Gao et al, 2013;Tang et al, 2017;Tang et al, 2019).…”
Section: Overview Of Fgfs and Fgfrsmentioning
confidence: 99%
“…The FGF19 subfamily consists of FGF15/19, FGF21, and FGF23. Although Fgf15/19, FGF21, and FGF23 have only about 22-35% amino acid identity, phylogenetic and gene locus analyses suggested that they belong to one subfamily Ornitz, 2004, 2008;Mikhaylenko et al, 2018). FGF15 and FGF19 are the mouse and human orthologs, respectively, which share 53% amino acid homology.…”
Section: Fgf19 Subfamilymentioning
confidence: 99%
“…Although differences between CTC and ctDNA genotyping and discordant genotypes between tumor biopsy and blood-based analyses were recognized, these disagreements are due to the methodological differences in isolation (Schechter et al, 2015;Sundaresan et al, 2016). Thus, it is known that the DNA isolation for a liquid biopsy varies due to tumor-specific mutations in DNA isolated from other cells present in the urine or the fluid itself (Mikhaylenko et al, 2018).…”
Section: Dna Sequencingmentioning
confidence: 99%